Thin film deposition of organic-inorganic quinoline-tin dioxide p-n junction for optoelectronic devices - Lucas P. Fonseca; Natália C. Oliveira; Lucas M. Martins; Luis V.A. Scalvi (Optical Materials: X)
Tin dioxide (SnO2) is an oxide semiconductor with n-type characteristics, with high transparency in the UV–Vis, where the donors are usually associated with oxygen vacancies and interstitial tin ions. Quinoline derivatives (QD) are usually p-type semiconductors with emission in the blue range. We report photo-induced properties of the QD 4-(6-(diethylamino)-4-phenylquinolin-2-yl)benzoic acid and the combination with the inorganic semiconductor oxide SnO2, both layers in the form of thin film, which forms a heterostructure. Thin film is a very convenient format for integration in optoelectronics. Emission of the QD takes place in blue range (470–485 nm) and depends on the solvent when in solution, being used acetone and tetrahydrofuran (THF). However, when in the form of thin film, it does not depend on the solvent. Concerning the heterostructure, it is explored under distinct device architecture: 1) combination in a transport profile perpendicular to the films (transverse contacts) leading to a rectifying behavior similar to a p-n junction, which is evidence of the p-type-like electrical behavior of the QD; 2) in parallel conduction profile, where there seems to exist some sort of interfacial phenomenon similar to a two-dimensional electron gas (2-DEG), a property that can be explored in transparent high-mobility transistors.